Empowerment of Women Through Entrepreneurship Workshops and Business Plan Development in Students of Babakan Ciwaringin Islamic Boarding School, Cirebon - Alfatih Sikki Manggabarani; Munashiron Miftah; Suryani Maryam (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
This training activity aims to improve the trainees' soft and hard skills, namely Members and administrators of the Cirebon district cottage. The output of the activity is an understanding of the importance of the role of women in doing business and entrepreneurship as an alternative to improve family welfare. Independence in earning a living can reduce dependence on men. This activity began with an initial survey and discussion with the board of the Islamic boarding school. This activity is carried out to get input and design activities needed by the training participants. This training activity uses the method: lectures and discussions.